2002
DOI: 10.1128/jb.184.9.2546-2551.2002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Heat Shock Response of Neisseria meningitidis with cDNA- and Oligonucleotide-Based DNA Microarrays

Abstract: Oligonucleotide-and cDNA-based microarrays comprising a subset of Neisseria meningitidis genes were assessed for study of the meningococcal heat shock response and found to be highly suitable for transcriptional profiling of N. meningitidis. Employing oligonucleotide arrays encompassing the entire genome of N. meningitidis, we analyzed the meningococcal heat shock response on a global scale and identified 55 heat shockderegulated open reading frames (34 induced and 21 repressed).Sequencing of the genomes of Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…Biological experiments and subsequent hybridizations were repeated five times, and data of the independent experiments were combined. ORFs, minimally exhibiting a 1.6-fold deregulation on average and being deregulated more than 1.6-fold in at least three experiments, were defined as differentially transcribed; this cutoff is based on previous results which showed a 1.6-fold difference to be detected at a level of confidence of above 99.7% (13).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological experiments and subsequent hybridizations were repeated five times, and data of the independent experiments were combined. ORFs, minimally exhibiting a 1.6-fold deregulation on average and being deregulated more than 1.6-fold in at least three experiments, were defined as differentially transcribed; this cutoff is based on previous results which showed a 1.6-fold difference to be detected at a level of confidence of above 99.7% (13).…”
Section: Methodsmentioning
confidence: 99%
“…The adherent bacteria were subsequently dissociated from host cells by treatment with trypsin-EDTA and harvested by centrifugation. RNA was isolated from the neisserial pellet as described previously (13). Control bacteria were treated identically to bacteria from infections, i.e., all incubations, and wash and centrifugation steps were performed, except that no host cells were present during incubation in RPMI medium with FCS (HBMEC controls) or without FCS (HEp-2 controls).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) The frpB promoter regions were amplified from each of the strains described above and sequenced, and the sequences and elements inferred from the experimentally mapped ϩ1 transcriptional start site in the present study are reported and reveal a phase-variable C tract between the Ϫ10 and Ϫ35 promoter elements in the strains. 20,25). In the present study, we used comparative transcriptome analysis of the Fur-null mutant to identify target genes affected directly and indirectly by this regulator, and as such we have begun to dissect the regulatory networks of the Fur protein and its role in global responses in N. meningitidis.…”
Section: Vol 188 2006mentioning
confidence: 99%
“…With the availability of whole genome sequences, the global response to temperature increase has been studied at the transcriptional level in diverse bacteria, from model organisms such as E. coli (45) and Bacillus subtilis (22), through the bioremediation-involved bacterium Shewanella oneidensis (16), to diverse mammalian pathogens such as Campylobacter jejuni (51), group A Streptococcus (50), Mycoplasma pneumoniae (59), Yersinia pestis (33), and Neisseria meningitidis (19). These global analyses revealed not only the induction of the classical Hsps but also changes in the expression levels of genes related to other cellular functions, such as flagellum biogenesis, transcriptional regulation, phage-related proteins, membrane composition, and pathogenesis, to cite a few.…”
mentioning
confidence: 99%